ANALISIS KESESUAIAN PENGEMBANGAN HUTAN KEMASYARAKATAN DI WILAYAH KPHP MODEL SINTUWUMAROSO DESA KILO KECAMATAN POSO PESISIR UTARA - Bernid Mebunde; Adam Malik; Imran Rachman (Universitas Tadulako, 2015)
Indonesia is rich of forest since years ago strongly interacted with forest, the forest and human have become unity. Many human needs can be fulfilled by forest such as housing, clothing, food, medicines, and environment service. Forest management is done to provide benefits for society generally and for people surroundings particularly. The benefits can be performed through planning and management optimally as the forest functions. The right determination of forest management is done to make forest useful optimally for the society either directly or indirectly. The regulation No. 41 Year 1999 stipulating that forming area of forest management of levels such as province, city,and unit namely forest management unit (KPH) as the main functions and to destiny for. The implementation of forest management in KPH become the fulfillment to conduct forest management covering forest arrangements activity, government effort emphasizing regulation is the publishing of government regulation No. 6/2007 jo PP 3 Year 2008 about Forest Arrangement, Forest Management Planning, and Forest Utilization explaining KPH covering Conservation KPH (KPHK), Preservation KPH (KPHL), and Production KPH (KPHP). The research was conducted at Society Forest of Kilo Village, Poso Pesisir Utara Sub district of Poso Regency. It was from June to August 2014. The data source obtained were observation and interview which directly observe the object examined and asking and answering by using questions guidence formed questionnaire. The result indicates that the location of biophysical condition is very exactly to utilize for forest production not plants forest wood with rubber types because it can give ecology benefits for environment improvement and re-optimizing forest function. The development of HKm formed society empowerment in Kilo village is as suitable with the economy social of society because make benefits for society income Key Wods: Analysis, Development, Society Forest, KPHP